Women's Contribution to Cassava Cultivation and Household Fund Allocation in Rural Lampung - Sri Indaryati; Dewi Utari; Novia Ambar Sari (Jurnal Studi Multidisiplin Ilmu, 2025)
Purpose: This study examines the contribution of women to cassava (Manihot esculenta) cultivation in Teluk Dalem Ilir Village, Rumbia Subdistrict, Central Lampung Regency, Indonesia, and analyzes how the economic value of their labor is allocated within the household economy.Methodology: A qualitative descriptive design was applied using snowball sampling to recruit 83 women who assist their husbands in cassava farming. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed following the interactive model of data reduction, data display, and conclusion drawing and verification.Results: Women contributed labor across land preparation, seedling planting, and maintenance activities, averaging 40.41 hours per production season and generating an estimated contribution value of IDR 406,566 per harvest. The largest share, IDR 138,089 (34%), was allocated to agricultural inputs, followed by educational needs and staple food purchases. Women's involvement accelerated cultivation tasks but reduced the time available for domestic responsibilities such as sweeping, laundry, and childcare. Conclusions: Women's labor is economically material yet remains informally recognized within household and community accounting systems.Limitations: The single-village, cross-sectional, self-reported design constrains generalizability and causal inference.Contributions: The study contributes empirical time-use and monetary-valuation evidence on women's often-invisible agricultural labor in a smallholder cassava system, offering a basis for genderresponsive extension and rural policy design.